Hemodynamic Consideration of Intracranial Aneurysm. (December 2017) - Ujiie, Hiroshi; Shinohara, Chie; Tamano, Yoshinori; Katou, Kouichi; Teramoto, Akira
We reviewed basic considerations in fluid dynamics of cerebral aneurysms and applied these in surgery on the three most common types: internal carotid-posterior communicating artery, middle cerebral artery, and anterior communicating artery. It was found that aneurysmal initiation and growth do not occur at symmetric bifurcations. As blood flow always obeys the law of inertia, jet flow into the aneurysm will disperse along the wall; assuming the aneurysmal wall strength is even, the shape of the aneurysm becomes round or oval. When neurosurgeons encounter an aneurysm that is not round or oval, the wall may be fragile and requires great care during surgical manipulation.